Outcome measures for determining treatment efficacy in radiculopathy - K., Shamna; C. S., Manju (International Journal of Basic & Clinical Pharmacology, 2025)
Radiculopathy is a neurological disorder caused by any pathology affecting the nerve roots of peripheral nerve system, commonly manifested by pain, paresthesia and motor weakness. Lumbosacral radiculopathy, commonly referred to as low back pain, and cervical radiculopathy, referred to as neck pain, are the two most common forms of the condition. Although one of the main goals of treatment is pain alleviation, this does not always indicate that a patient has entirely recovered. Even after their pain subsides, many patients still struggle with everyday activities and emotional wellbeing. Patient reported outcomes are therefore used to determine if the treatment is effective in terms of functional quality of life of the patient. There are several scales and questionnaires available to evaluate pain and functional disability in both cervical and lumbar radiculopathies. By using these measures, efficacy of treatment may be evaluated more precisely and patient care is enhanced.